Using Orthogonal Combined Signals in Broadband ADCP for Improving Velocity Measurement - Yujing Lin; Fei Yuan; En Cheng (Journal of Marine Science and Engineering, 2020)
Broadband Acoustic Doppler Current Profiler (BBADCP) is a widely used technology in velocity measurements. To adapt to the varied water environment and different measurement requirements, flexible tuning of transmitted signal parameters will improve the feasibility and accuracy of velocity measurement. Compared with the conventional signal, the orthogonal combined signal designed in this paper can generate a wealth of signal combination examples and improve the accuracy of the velocity measurement under the same conditions. The proposed orthogonal combined signal consists of two orthogonal sub-signals with a symmetrical spectrum. Each is designed based on time delay to eliminate or weaken the current velocity ambiguity. Then, the processing method of the received signal when the pulse signals are the same or different coded signal is discussed. The numerical simulation results show that, when using the proposed method, the standard deviation of the estimated current velocity has different degrees of reduction at different current velocities. Our simulation also shows that, compared to the convention method, the proposed method can improve the SNR by 10 dB. This can help significantly increase the scope of the configuration.